NARIVETTA AS NECROPOLITICAL CRITIQUE OF THE INDIAN STATE: SOVEREIGN POWER, UNGRIEVABLE LIVES, AND THE AESTHETICS OF ADIVASI RESISTANCE - M, Saumi Mary; RK, Dhanya Ravindran (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Anuraj Manohar’s feature film Narivetta (2025) functions simultaneously as a work of cinema and as an act of political testimony. Drawing its narrative from the 2003 Muthanga tribal protest in Kerala—one of the most consequential and deliberately obscured episodes of state violence in postcolonial India—the film stages a rigorous cinematic interrogation of the Indian democratic state’s relationship with its indigenous Adivasi communities. This paper argues that Narivetta constitutes a fully realized necropolitical critique: a sustained indictment of how the sovereign state exercises its ultimate power not merely to govern life, but to determine whose life may be extinguished and whose death may be erased. Drawing on Achille Mbembe’s theory of necropolitics alongside Giorgio Agamben’s conceptualization of bare life and the state of exception, and Judith Butler’s framework of grievability, this analysis identifies four interconnected cinematic manifestations of necropolitical governance. These include the strategic transformation of the remote Wayanad forest into a permanent zone of exception; the construction of the Adivasi body as simultaneously hypervisible threat and constitutionally invisible citizen; the cold institutionalization of bureaucratic death-rationale through state agencies; and the deployment of development discourse as ideological cover for systemic land dispossession. The film further employs a distinctive set of subaltern aesthetics—handheld documentary realism, muted palettes of bare life, and the deliberate withholding of subtitles during tribal-dialect dialogue—to replicate, at the level of form, the very epistemic exclusion the narrative critiques at the level of content. By reframing Adivasi deaths as acts of political defiance rather than mere collateral damage, Narivetta constructs an essential counter-archive against the state’s strategy of statistical denial and historical erasure, ensuring that the silenced dead of Muthanga are not merely mourned but remembered as agents of unfinished resistance.